Indigenous and Parks Canada Agency perspectives on the management of Gulf Islands National Park Reserve - Fitzsimmons, Andrew (2021)
Graduate In the Gulf Islands and Salish Sea Regions of British Columbia the Parks Canada Agency (PCA) currently operates Gulf Islands National Park Reserve (GINPR) and is in the development phase for the proposed Southern Strait of Georgia National Marine Conservation Area Reserve (SSGNMCAR). Protected areas such as these are meant to protect the ecological and cultural heritage of the region on behalf of all Canadians. As the government runs and expands their protected areas in the region it is important to look at their relationship with Indigenous communities in particular, as the PCA mandate requires the agency to work in “partnership” with Indigenous communities (Parks Canada 2017). The region is home to nearly 20 First Nations groups including the three W̱SÁNEĆ First Nations of the W̱SÁNEĆ Leadership Council (WLC). The WLC is an Indigenous government that has publicly stated their perception of a strained relationship with the PCA beginning before the formal establishment of GINPR in 2003. Through historical analysis; interviews with employees from the PCA and members of the W̱SÁNEĆ community; and a review of several aspects of site management and establishment in the region – this thesis explores the changing relationship between the PCA and W̱SÁNEĆ First Nations. Through this thesis I collect and discuss recommendations from W̱SÁNEĆ community members, and develop several myself, for the PCA to consider developing to improve the partnership between the two bodies. Potentially a partnership could lead towards formalized and lasting co-operative decision-making practice in the region’s cultural and natural heritage management.